2018
DOI: 10.1016/j.critrevonc.2018.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of whole body magnetic resonance imaging (WBMRI) to whole body computed tomography (WBCT) or 18 F-fluorodeoxyglucose positron emission tomography/CT ( 18 F-FDG PET/CT) in patients with myeloma: Systematic review of diagnostic performance

Abstract: Studies were heterogeneous, the majority lacking an independent reference standard. Future prospective trials should address these limitations and assess the impact of WBMRI on management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 49 publications
(38 reference statements)
1
24
0
1
Order By: Relevance
“…Therefore, more sensitive imaging techniques for the diagnosis and follow-up of MM have been described, such as WBLDCT, MRI and PET/CT. Wholebody MRI and 18F-fluorodeoxyglucose-PET/CT have been described to be more accurate in detecting bone lesions in MM as compared to skeletal surveys [8][9][10][11][12][13][14], and wholebody MRI have been found to detect significantly more MM bone involvement compared to PET/CT [12]. Whole-body MRI and PET/CT are, however, limited in their availability and are relatively costly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, more sensitive imaging techniques for the diagnosis and follow-up of MM have been described, such as WBLDCT, MRI and PET/CT. Wholebody MRI and 18F-fluorodeoxyglucose-PET/CT have been described to be more accurate in detecting bone lesions in MM as compared to skeletal surveys [8][9][10][11][12][13][14], and wholebody MRI have been found to detect significantly more MM bone involvement compared to PET/CT [12]. Whole-body MRI and PET/CT are, however, limited in their availability and are relatively costly.…”
Section: Discussionmentioning
confidence: 99%
“…However, the value of conventional radiographs in detecting osteolytic lesions is limited since at least 30% of trabecular bone must be destroyed to be visible by radiograph [7]. Cross-sectional imaging techniques such as computed tomography (CT), magnetic resonance imaging (MRI) and integrated positron emission tomography/CT (PET/CT), have proven to be more accurate in detecting osteolytic and marrow replacing lesions as compared to skeletal surveys using radiographs [8][9][10][11][12][13][14]. As a result, more accurate diagnosis, staging and follow-up of MM is possible [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…A recent systematic review compared whole-body MRI and FDG PET/CT in their ability to detect myeloma skeletal lesions and suggested that MRI is more sensitive but less specific than FDG PET/CT. Yet, it also concluded that most of the included studies were heterogeneous and lacking an independent reference standard [47].…”
Section: The Evolving Role Of Fdg-pet/ct In Multiple Myelomamentioning
confidence: 99%
“…While the guidelines state that [ 18 F]FDG‐PET/CT should be considered the preferred imaging technique to evaluate and monitor metabolic response to therapy in MM, there are presently no studies that directly compare [ 18 F]FDG‐PET/CT with WB‐DWI or DCE‐MRI. A recent systematic review concluded that data on this topic are too heterogeneous, with biased accrual, and lack an independent reference standard, which also precluded a meta‐analysis . Therefore, it remains unclear which test may be best for response assessment.…”
Section: Myelomamentioning
confidence: 99%